Re-evaluation of microscopy confirmed Plasmodium falciparum and Plasmodium vivax malaria by nested PCR detection in southern Ethiopia - Mekonnen, Seleshi Kebede (BioMed Central, 2014)
BACKGROUND: With 75% of the Ethiopian population at risk of malaria, accurate diagnosis is crucial for malaria treatment in endemic areas where Plasmodium falciparum and Plasmodium vivax co-exist. The present study evaluated the performance of regular microscopy in accurate identification of Plasmodium spp. in febrile patients visiting health facilities in southern Ethiopia. METHODS: A cross-sectional study design was employed to recruit study subjects who were microscopically positive for malaria parasites and attending health facilities in southern Ethiopia between August and December 2011. Of the 1,416 febrile patients attending primary health facilities, 314 febrile patients, whose slides were positive for P. falciparum, P. vivax or mixed infections using microscopy, were re-evaluated for their infection status by PCR. Finger-prick blood samples were used for parasite genomic DNA extraction. Phylogenetic analyses were performed to reconstruct the distribution of different Plasmodium spp. across the three geographical areas. RESULTS: Of the 314 patients with a positive thick blood smear, seven patients (2%) were negative for any of the Plasmodium spp. by nested PCR. Among 180 microscopically diagnosed P. falciparum cases, 111 (61.7%) were confirmed by PCR, 44 (24.4%) were confirmed as P. vivax, 18 (10%) had mixed infections with P. falciparum and P. vivax and two (1.1%) were mixed infections with P. falciparum and P. malariae and five (2.8%) were negative for any of the Plasmodium spp. Of 131 microscopically diagnosed P. vivax cases, 110 (84%) were confirmed as P. vivax, 14 (10.7%) were confirmed as P. falciparum, two (1.5%) were P. malariae, three (2.3%) with mixed infections with P. falciparum and P. vivax and two (1.5%) were negative for any of the Plasmodium spp. Plasmodium falciparum and P. vivax mixed infections were observed. Plasmodium malariae was detected as mono and mixed infections in four individuals. CONCLUSION: False positivity, under-reporting of mixed infections and a significant number of species mismatch needs attention and should be improved for appropriate diagnosis. The detection of substantial number of false positive results by molecular methodologies may provide the accurate incidence of circulating Plasmodium species in the geographical region and has important repercussions in understanding malaria epidemiology and subsequent control.